EFFECT OF BACK EXERCISE TO DECREASE LOW BACK PAIN OF BATIK ARTISANTS IN KAUMAN VILLAGE, SOKARAJA - harwanti, siti; Aji, Budi; Ulfah, Nur (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2019)
ABSTRACT Low back pain ( LBP ) is a musculoskeletal disorder that occurs in the lower back which can be caused by various diseases and  activity of the body being less good. One effort to overcome the LBP is back exercise. The research purpose is to find out the effect of back exercise therapy which concern to lowering painful complaint of batik artisants in Kauman village Sokaraja subsdistrict. This research is using Quasi Experiment technique phenomenological non equivalen control group design (pre -post test). Sample taking is using purposive sampling technique. Data analysis use Friedman experiment for treatment group and Repeated Annova experiment for control group. Experiment analysis is different between treatment group and control group with using Mann Whitney experiment. The result of Friedman experiment in treatment group shows that p-value=0,000(p<0,05), it means the therapy those given is effective to lowering painful complaint. The result of Repeated Annova experiment in control group shows that p-value=0,234(p>0,05), it means the painful complaint seems not different in control group. The result of Mann Whitney experiment shows that p-value=0,000(p<0,05) it means there are differences between painful complaint in treatment group and control group after doing back exercise. There is the effect by giving back exercise therapy which concern to lowering the complaint of low back pain for batik artisants in Kauman village Sokaraja subdistrict.   Key words: Handmade Batik, Low back pain, back exercise